Newton method in the context of quaternion analysis - Falcão, M. I. (2014)
In this paper we propose a version of Newton method for finding zeros of a quaternion function of a quaternion variable, based on the concept of quaternion radial derivative. Several numerical examples involving elementary functions are presented.